Seismic evidence for proterozoic collisional episodes along two geosutures within the southern granulite province of India - Prathigadapa, Raju; Sharma, Subrata Das; Ramesh, Durbha Sai (My University, 2020)
The Southern Granulite Province of India had witnessed episodes of multiple tectonic activities, leading to sparsely preserved surface geological features. The present study is focused on unraveling the geodynamic evolution of this terrain through measurement of Moho depth and Vp/Vs ratio using data from a large number of broadband seismic stations. These results unambiguously establish three domains distinct in Moho depth and crustal composition. An intermediate to felsic crust with a 7–10 km step-in-Moho is delineated across the Moyar–Bhavani region. Anomalously high felsic crust with abrupt jump in Moho (~8–10 km) together with a dipping feature at deeper level characterizes the transition from eastern to southern segments of the Jhavadi–Kambam–Trichur region. By contrast, the central zone hosting the Palghat–Cauvery shear zone records uniform felsic crust and flat Moho. Drawing analogy from similar results in different parts of the globe, juxtaposition of petrologically dissimilar crustal blocks characterized by varied depths to the Moho is argued to point towards unambiguous presence of two distinct geosutures in the study area: one along the Moyar–Bhavani region and the other across the Jhavadi–Kambam–Trichur. This inference is corroborated by the presence of layered meta-anorthosite, related rock suites, and mafic-ultramafic bodies, supporting the view of a suprasubduction setting in the Moyar–Bhavani region. The Jhavadi–Kambam–Trichur area is marked by operation of the Wilson cycle by way of sparsely preserved geological features such as the presence of ophirags (ophiolite fragments), alkali syenites, and carbonatites. Geochronological results suggest that the suturing along Moyar–Bhavani took place during the Paleoproterozoic and that along Jhavadi–Kambam–Trichur was during the late Neoproterozoic.
Keywords: Geosutures; Seismic evidence; Proterozoic Collisional Episodes